VALIDASI METODE ANALISIS POLISIKLIK AROMATIK HIDROKARBON (PAH) DALAM SEDIMEN DI SEKITAR PANTAI MAKASSAR - Muhammad Syahrir; Nurul Hidayat Aprilita; Nuryono Nuryono (Jurnal Kimia Terapan Indonesia, 2015)
Validation of  analysis  method of PAH have been done in marine sediment of Macassar Coast by Gas Chromatography (GC-FID). Validation of method include:  limit of detection (LoD), limit of quantification (LoQ) and linearity range. The results of validation method of 7 types PAHs (Naphtalene, Acenaphtene, Penanthrene, Fluoranthene, Pyrene, Benzo (a) Anthracene and perylene) give  a  linearity  range between 0.5 to 20 ppm with an average linearity approaches a value of 1. LoD for  Naphtalene; Acenaphthene; Penanthrene; Fluoranthene; Pyrene; Benzo (a) Anthracene; and Perylene are  3.541; 0.208; 1,736; 1.737; 1,738; 12.124; and 2,128 ppm, respectively. LoQ for Naphtalene; Acenaphthene; Penanthrene; Fluoranthene; Pyrene; Benzo (a) Anthracene; and Perylene are  11,803; 0.695; 5.786; 5.786; 5.788; 5.794; 7.0796 and 7.092 ppm, respectively. Limit of detection (LoD), limit of quantification (LoQ), linearity and linear range can be used to determine the concentration of PAH in sediment samples.Keywords: Validation Method, Concentration, PAH, Sediments